Description of the females of Niganda phichai and Saliocleta puyak (Lepidoptera: Notodontidae, Ceirini), with breedings of both species - Pellinen, Markku J. (Zootaxa, 2019)
Female specimens of Niganda phichai Pellinen 2012 and Saliocleta puyak Pellinen 2017, were detected by author during last years collecting with mixed -and uv-light lamps in Northern-Thailand.